Innovative Reinforced Soil Structures for High Walls and Slopes Combining Polymeric and Metallic Reinforcements. (2015) - Lelli, Matteo; Laneri, Riccardo; Rimoldi, Pietro
Abstract: The aim of the paper is to describe the main advantages of using innovative engineered systems to build reinforced soil structures compared to traditional ones. In particular the paper refers to "hybrid" systems which combine planar polymeric reinforcements (geogrids) and steel wire mesh units in order to build high MSE walls (inclination ≥ 70°, up to almost 90°) or slopes (inclination < 70°). Both the components act as reinforcements and as stabilizing elements. Geogrids are considered to work as primary reinforcements since they guarantee the overall and compound internal stability of the structure. Whereas the wire mesh units are considered a secondary reinforcement providing the local stability at the facing, ensuring that no local mechanism of direct sliding, pull-out or rotational failure occurs. Results on existing structures indicate that, as structures achieve relevant heights (above 10 m), there is a large potential for cost effectiveness in using wire mesh and grids combined, in place of a 100% geogrids or a 100% steel mesh reinforcement solution only[1, 2] . Very high hybrid structures have been built all over the world following the mentioned approach. With this paper, three relevant case histories are presented. Firstly, a 80 m high reinforced soil hybrid structure built as retaining structure for a new airport construction in India. Secondly, a 40 m high reinforced soil hybrid structure, built as support for the construction of a highway in Albania. Thirdly, a reinforced soil hybrid structure, up to 16 m high, built as support for heavy tanks of an oil refinery in Turkey, which has been recently fully instrumented.